KEMENANGAN LUKMAN EDY-SURYADI KHUSAINI DI KECAMATAN PERHENTIAN RAJA PADA PILGUB PUTARAN PERTAMA TAHUN 2013 - Tatin Ambari; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Successful team must be set up with a good candidate determination of campaigners, target and analysis of community needs, how to compose messages that campaign as well as media selection and deployment of media effectively and efficiently. Successfully recruited a team of workers potentially amenable duties and functions. Internal consolidation campaign team is done by holding preparatory meetings before and during the campaign. The preparation includes strengthening party networks to the board on the Villages to Hamlet-Hamlet, preparation of witnesses in each polling station, monitoring the development of competitors in each village, and budgeting search campaign finance, media and techniques election campaign, as well as raising mass for the campaign. The more interesting the messages conveyed in the media, then the public would be interested anyway to listen or understand. communication techniques should be considered in the general election by using the mass media. Medium or forum is a vehicle is selected in the campaign. For the print media could be newspapers, magazines, leaflets, or flyers. As for the electronic media can use television, radio, VCD, internet or mobile phone.Keywords: Victory, Lukman Edy-Suryadi Khusaini, Pilgub, First Round